2006
DOI: 10.1111/j.1742-4658.2006.05329.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tyrosine‐phosphorylation sites in the nuclear membrane protein emerin

Abstract: The nuclear envelope encloses the genetic material of a eukaryotic cell and takes part in its structural and functional organization. It consists of interconnected membranes, an outer nuclear membrane (ONM) and an inner nuclear membrane (INM). The ONM is part of the rough endoplasmic reticulum and folds at the nuclear pores into the INM, which is firmly attached to the lamina by integral membrane proteins of the INM. The INM proteins form complexes, transiently or stably, with lamins, chromatin proteins and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
(70 reference statements)
1
13
0
Order By: Relevance
“…We compiled data from 13 independent proteomic studies (Amanchy et al, 2005;Brill et al, 2004;Cantin et al, 2008;Daub et al, 2008;Guo et al, 2008;Olsen et al, 2006;Pan et al, 2008;Rikova et al, 2007;Rush et al, 2005;Schlosser et al, 2006;Sui et al, 2008;Tao et al, 2005;Tsai et al, 2008), which identified 13 phosphorylated tyrosines in emerin (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We compiled data from 13 independent proteomic studies (Amanchy et al, 2005;Brill et al, 2004;Cantin et al, 2008;Daub et al, 2008;Guo et al, 2008;Olsen et al, 2006;Pan et al, 2008;Rikova et al, 2007;Rush et al, 2005;Schlosser et al, 2006;Sui et al, 2008;Tao et al, 2005;Tsai et al, 2008), which identified 13 phosphorylated tyrosines in emerin (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…If so, what might be the function of this sumoylated pool of PTP1B? Certain proteins of the INM, including emerin and lamin A/C, are known to be tyrosine phosphorylated Schlosser et al, 2006). Unlike the analogous cell-cycle-dependent serine/threonine phosphorylations (Ellis et al, 1998;Fields and Thompson, 1995), the physiological relevance of these tyrosine phosphorylations are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are clues that hint at significant functions for these modifications. For example, Tyr95 in emerin has been mapped as a site of tyrosine phosphorylation (Schlosser et al, 2006). This site lies within a small region (amino acids 95-99) that is deleted in some forms of X-chromosome-linked EDMD (Bengtsson and Wilson, 2004;Ellis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations